Comparison of zinc oxide and eugenol, and Vitapex for root canal treatment of necrotic primary teeth - M. MORTAZAVI & M. MESBAHI (Paediatric Dentistry, 2004)
The aims of this study were to evaluate iodoform base materials for root canal treatment of necrotic primary teeth, and to compare them with traditionally used zinc oxide and eugenol (ZOE).